Liver transplantation for unresectable Klatskin tumor: first long-term outcomes – a single center experience - D. A. Granov; I. I. Tileubergenov; A. R. Sheraliev; V. N. Zhuikov; A. A. Polikarpov; A. V. Moiseenko (Вестник трансплантологии и искусственных органов)
Objective: to demonstrate the first long-term outcomes of treatment of unresectable hilar cholangiocarcinoma (HCCA) after combined neoadjuvant therapy followed by liver transplantation (LT). Materials and methods. From 2017 to 2023, at the Russian Research Center of Radiology and Surgical Technologies, 10 patients were included in the treatment protocol for unresectable HCCA. Combined neoadjuvant therapy included endobiliary photodynamic therapy (EPDT), regional chemotherapy (RCT) and systemic polychemotherapy (SPCT). Each modality was applied at least three times over a period of four to six months. Patients were placed on the LT waitlist when tumor marker CA19-9 reduced, there was no radiological evidence of disease progression, and there was no evidence of acute cholangitis. Before LT, the recipients underwent diagnostic laparoscopy to exclude carcinomatosis and also evaluation of regional lymph nodes with urgent morphologic examination. In the absence of extrahepatic tumor spread, LT from a deceased donor was performed according to the classical technique with paracaval and hepatoduodenal lymph node dissection, biliodigestive anastomosis using the Roux-en-Y procedure. The operation was performed in six patients. Patient age ranged from 40 to 55 years (mean, 46.3). The mean time from start of treatment to LT was 9.1 months (range 6 to 14). The mean CA19-9 level at the time of LT was 66.5 IU/mL (8 to 212). Results. After combined neoadjuvant treatment, the CA19-9 marker normalized in four patients and there was a 3–4-fold decrease in two patients. Radiological evaluation indicated stable disease in five patients, and a partial response in one. Disease progression was noted in four out of 10 patients. Currently, one of the 6 patients is alive with a follow-up of 34 months. Median (Me) overall survival is 28 months; Me overall survival after LT is 22.2 months; Me survival before progression is 27 months. During long-term follow-up of patients after LT, three patients out of six had disease progression: implantation metastasis (n = 2) at 25 and 27 months follow-up (metastasectomy was performed), carcinomatosis (n = 1) at 20 months follow-up. Conclusion. LT for unresectable Klatskin tumor is effective when combined neoadjuvant treatment is used and there is no acute cholangitis. However, the use of endobiliary manipulations (drainage change, EPDT) are risk factors for the development of implantation metastasis.